2013
DOI: 10.1016/j.theriogenology.2012.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Equine chorionic gonadotropin alters luteal cell morphologic features related to progesterone synthesis

Abstract: Exogenous eCG for stimulation of a single dominant follicle or for superovulation are common strategies to improve reproductive efficiency by increasing pregnancy rates and embryo production, respectively. Morphofunctional changes in the CL of eCG-treated cattle include increases in CL volume and plasma progesterone concentrations. Therefore, we tested the hypothesis that eCG alters the content of luteal cells and mitochondria related to hormone production. Twelve crossbred beef cows were synchronized and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 37 publications
0
17
1
3
Order By: Relevance
“…Treatment with letrozole may have resulted in an increase in luteal cell numbers or an alteration in the proportion of small and large luteal cells within the CL and an increase in progesterone-producing capability per CL volume. In this regard, treatment of cows with equine chorionic gonadotropin resulted in increased density and number of large luteal cells which increased the capacity of the CL to produce progesterone [37]. Although we were unable to document the effect of letrozole treatment on gonadotropin secretion in the present study, previous studies have shown an increase in gonadotropin secretion after single or 3-day letrozole regimen [15,38,39].…”
Section: Discussioncontrasting
confidence: 53%
“…Treatment with letrozole may have resulted in an increase in luteal cell numbers or an alteration in the proportion of small and large luteal cells within the CL and an increase in progesterone-producing capability per CL volume. In this regard, treatment of cows with equine chorionic gonadotropin resulted in increased density and number of large luteal cells which increased the capacity of the CL to produce progesterone [37]. Although we were unable to document the effect of letrozole treatment on gonadotropin secretion in the present study, previous studies have shown an increase in gonadotropin secretion after single or 3-day letrozole regimen [15,38,39].…”
Section: Discussioncontrasting
confidence: 53%
“…Some authors have shown that it can increase preovulatory follicle size and that would end up in a larger Cl (tORtERElla et al, 2013). the size of the Cl is important for progesterone secretion and pregnancy maintenance (RIGOGlIO et al, 2013;MaRtINEZ et al, 2014). however, in previous studies eCG did not influence pre-ovulatory follicle size however it rather enhanced Cl size (BaRUSEllI et al, 2004;pUllEY et al, 2013;MaRQUEZINI et al, 2014).…”
Section: Discussionmentioning
confidence: 87%
“…an increase in progesterone concentration has also been described as a positive effect of the eCG (SaNtOS et al, 2001;BaRUSEllI et al, 2004;MaRQUEZINI et al, 2014). the eCG acts increasing the number of lutheal cells and mitochondrias that in turn increases pregnenolone synthesis (RIGOGlIO et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The greater weight of CL can be due to the increase in the LF at TAI (Sá Filho et al, 2010b), an increase in the number of large luteal cell or an increase in the proportion between large and small luteal cells (Rigoglio et al, 2012). However, although eCG-treated cows presented larger and heavier CLs, these cows did not present a higher concentration of P4 in the dioestrus.…”
Section: Resultsmentioning
confidence: 95%